2012
DOI: 10.1038/nn.3100
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for direct and indirect pathway striatal neurons in reinforcement

Abstract: Dopamine signaling is implicated in reinforcement learning, but the neural substrates targeted by dopamine are poorly understood. Here, we bypassed dopamine signaling itself and tested how optogenetic activation of dopamine D1- or D2-receptor-expressing striatal projection neurons influenced reinforcement learning in mice. Stimulating D1-expressing neurons induced persistent reinforcement, whereas stimulating D2-expressing neurons induced transient punishment, demonstrating that activation of these circuits is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
790
10
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 873 publications
(858 citation statements)
references
References 14 publications
55
790
10
3
Order By: Relevance
“…Notably, these findings persisted even in the presence of simulated DA blockade (simulated by altering the choice incentive parameter): Because learning effects of DA in the model result from activation of D1 or D2 MSNs, the learning asymmetry persists with DA blockade due to their direct stimulation. Importantly, this is not simply a null effect: the model does predict that DA blockade reduces the absolute number of actions selected, even without changing the relative preference between the actions; both of these effects accord well with the observations of Kravitz et al (2012; Figure 5). …”
Section: Simulating Optogenetic Effects On Learning and Performancesupporting
confidence: 78%
See 4 more Smart Citations
“…Notably, these findings persisted even in the presence of simulated DA blockade (simulated by altering the choice incentive parameter): Because learning effects of DA in the model result from activation of D1 or D2 MSNs, the learning asymmetry persists with DA blockade due to their direct stimulation. Importantly, this is not simply a null effect: the model does predict that DA blockade reduces the absolute number of actions selected, even without changing the relative preference between the actions; both of these effects accord well with the observations of Kravitz et al (2012; Figure 5). …”
Section: Simulating Optogenetic Effects On Learning and Performancesupporting
confidence: 78%
“…Importantly, this is not simply a null effect: the model does predict that DA blockade reduces the absolute number of actions selected, even without changing the relative preference between the actions; both of these effects accord well with the observations of Kravitz et al (2012; Figure 5). Finally, Kravitz et al (2012) reported that learning induced by D2 MSN stimulation was less robust and rapidly extinguished relative to D1 MSN stimulation. However we show here that their full pattern of results are obtained in the model without assuming any asymmetry in the robustness of learning per se.…”
supporting
confidence: 78%
See 3 more Smart Citations